2011
DOI: 10.1111/j.1365-313x.2010.04465.x
|View full text |Cite
|
Sign up to set email alerts
|

Members of an R2R3‐MYB transcription factor family in Petunia are developmentally and environmentally regulated to control complex floral and vegetative pigmentation patterning

Abstract: SUMMARYWe present an investigation of anthocyanin regulation over the entire petunia plant, determining the mechanisms governing complex floral pigmentation patterning and environmentally induced vegetative anthocyanin synthesis. DEEP PURPLE (DPL) and PURPLE HAZE (PHZ) encode members of the R2R3-MYB transcription factor family that regulate anthocyanin synthesis in petunia, and control anthocyanin production in vegetative tissues and contribute to floral pigmentation. In addition to these two MYB factors, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
386
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(398 citation statements)
references
References 68 publications
10
386
0
2
Order By: Relevance
“…This is consistent with the idea that MYB182 could have a negative effect on PA accumulation. Such negative correlations in developmental expression have been observed with AtMYBL2, PhMYB27, and VvMYBC2-L1 repressors (Dubos et al, 2008;Albert et al, 2011;Huang et al, 2014). We next used reverse transcription-quantitative PCR (RT-qPCR) to confirm that MYB182 expression is up-regulated in MYB134-overexpressing poplars, as this is how it was first identified (Supplemental Fig.…”
mentioning
confidence: 96%
“…This is consistent with the idea that MYB182 could have a negative effect on PA accumulation. Such negative correlations in developmental expression have been observed with AtMYBL2, PhMYB27, and VvMYBC2-L1 repressors (Dubos et al, 2008;Albert et al, 2011;Huang et al, 2014). We next used reverse transcription-quantitative PCR (RT-qPCR) to confirm that MYB182 expression is up-regulated in MYB134-overexpressing poplars, as this is how it was first identified (Supplemental Fig.…”
mentioning
confidence: 96%
“…Studies in snapdragon (Antirrhinum majus) and petunia (Petunia hybrida) have revealed a conserved mechanism for the formation of vein-associated anthocyanin pigmentation pattern in petal epidermis. Pigments are only produced in the overlapping expression domains of the R2R3-MYB and bHLH coregulators of anthocyanin biosynthetic genes; the bHLH expression is confined to the petal epidermis and the R2R3-MYB expression is specific to cells above the vascular bundles (8,12,13). However, the molecular basis of variation in this color pattern among natural species is less clear, although in the case of Antirrhinum, the R2R3-MYB, Venosa, was implicated as the causal gene, explaining much of the natural variation (8,12).…”
mentioning
confidence: 99%
“…Similarly, jasmonate ZIMdomain (JAZ) protein interacts with the PAP1-TT8/GL3-TTG1 complex and represses anthocyanin accumulation (Qi et al 2011). PhMYBx (R3-MYB) is also proposed to act as an inhibitor of anthocyanin biosynthesis in vegetative tissues of petunia (Albert et al 2014;Albert et al 2011). We have also isolated two single-repeat R3MYB transcription factors, GtMYB1R1 and GtMYB1R9, from a gentian petal cDNA library.…”
Section: Negative Regulators Of Anthocyanin Biosynthesis In Gentian Fmentioning
confidence: 99%
“…A few novel R2R3MYB genes have recently been characterized in petunia: DEEP PURPLE (DPL) regulating vein-associated anthocyanin pigmentation in flower tubes and PURPLE HAZE (PHZ) determining light-induced anthocyanin accumulation on exposed petal surfaces (bud-blush) (Albert et al 2011). In Asiatic hybrid lilies, LhMYB6 and LhMYB12 together with LhbHLH2 regulate anthocyanin pigmentation in specific organs (Yamagishi et al 2010).…”
Section: Transcription Factors Responsible For Anthocyanin Biosynthesmentioning
confidence: 99%